IMPROVEMENT OF THYROID GLAND CANCER DIAGNOSIS BASED ON ULTRASOUND DATA: A REVIEW - Sunnatullayeva , Nigina Djurabekovna (Educational Research in Universal Sciences, 2023)
Thyroid gland cancer is a prevalent type of cancer worldwide, and its incidence continues to rise. Early and accurate diagnosis of thyroid cancer is crucial for appropriate treatment, patient management, and prognosis. Ultrasound imaging is commonly used as a first-line diagnostic tool for thyroid cancer due to its non-invasive nature and ability to provide detailed anatomical and morphological information. However, accurate diagnosis solely based on ultrasound remains challenging, often leading to unnecessary surgeries or missed diagnoses. Therefore, this review aims to explore various approaches and advancements for improving the diagnosis of thyroid gland cancer using ultrasound data.